A potent drug candidature of Cu(II) pyrazino[2, 3‐f][1, 10]phenanthroline complexes with bioactive ligands: synthesis, crystal structures, biomolecular interactions, radical scavenging and cytotoxicities. Issue 18 (12th December 2021) - İnci, Duygu; Aydın, Rahmiye; Vatan, Özgür; Zorlu, Yunus
Abstract: A novel ternary copper(II) complexes, - [Cu(py-phen)(asn)(NO3 )(H2 O)] (1 ) and [Cu(py-phen)(trp)(H2 O)]NO3 (2 )- (py-phen: pyrazino[2, 3‐f][1, 10]phenanthroline, asn: asparagine, trp: tryptophan), have been synthesized and characterized by CHN analysis, ESI-MS, FTIR and single-crystal X-ray diffraction techniques. Interaction of the complexes 1 and 2 with CT-DNA has been investigated by absorption spectral titration, EB and Hoechst 33258 displacement assay. The interaction between the complexes 1 and 2 and BSA was investigated by electronic absorption and fluorescence spectroscopy methods. The experimental outcomes indicate that the fluorescence quenching mechanism between the complexes 1 and 2 and BSA is a static quenching process. The Stern-Volmer constants, binding constants, binding sites and the corresponding thermodynamic parameters (ΔG, ΔH, ΔS) of BSA + complex systems were determined at different temperatures. The binding distance between the complexes 1 and 2 and BSA was calculated according to FRET. The effect of the complexes 1 and 2 on the conformation of BSA was also examined using synchronous, two dimensional (2D) and three dimensional (3D) fluorescence spectroscopy. Radical scavenging activity of the complex was determined in terms of EC50, using the DPPH and H2 O2 method. The anticancer activities of the complexes 1 and 2 were investigated using an XTT assay against three cancer cell lines (MCF-7, Caco-2 and A549) and non-tumor cell line (BEAS-2B). Communicated by Ramaswamy H. Sarma Graphical abstract: A potent drug candidature of two new copper(II) complexes, - [Cu(py-phen)(asn)(NO3 )(H2 O)] (1 ) and [Cu(py-phen)(trp)(H2 O)]NO3 (2 )- (py-phen: pyrazino[2, 3‐f][1, 10]phenanthroline, asn: asparagine, trp: tryptophan), have been synthesized and characterized by CHN analysis, FTIR, ESI-MS and single-crystal X-ray diffraction techniques. The complexes have been tested for their in vitro biomolecular interactions by the spectroscopic methods. Furthermore, radical scavenging and anticancer activities of the complexes was also investigated. Highlights: A potent drug candidature of two new copper(II) complexes were synthesized and structurally characterized. Single crystal analysis of the two complexes was performed. The complexes interact with CT-DNA by a moderate intercalation binding mode. The quenching mechanism found between the complexes and BSA is a static type. The complexes demonstrate radical scavenging activity DPPH and H2O2 methods. Furthermore, the complexes exhibit anticancer activity against MCF-7, Caco-2 and A549 cell lines